Modified Algorithm for Calculating the Parameters of Maneuvers of Coplanar Meeting of Spacecraft in a Near-Circular Orbit Using Low-Thrust Engines - Andrey A. Baranov; Adilson P. Olivio (RUDN Journal of Engineering Research)
A modified algorithm is presented for solving the problem of spacecraft rendezvous in a near-circular orbit. The study considers the calculation of maneuver parameters executed on several turns using a low-thrust propulsion system. It is assumed that the active spacecraft performs maneuvers within a predefined region around the target spacecraft, while the perturbative effects of Earth’s gravitational field non-centrality and atmospheric drag are neglected. Well-established approximate mathematical models of spacecraft motion are employed to address the rendezvous problem. The methodology of determining the parameters of maneuvers is structured into three key stages: in the first and third stages, the parameters of impulsive transfer and low-thrust transfer are determined using analytical methods. In the second stage, maneuvers are allocated across the available turns to ensure a successful rendezvous by minimizing a selected control variable. The proposed approach is distinguished by its computational efficiency and robustness, making it suitable for onboard implementation in autonomous spacecraft navigation systems. As a case study, the paper analyzes the dependence of total characteristic velocity required for rendezvous on the magnitude of engine thrust and provides a comparative assessment of the total characteristic velocity for both impulsive and low-thrust maneuvering scenarios.